Marrying Body and Theology: A Response to Thomas Finegan - Lawler, Michael G. (Irish theological quarterly, 2024)
In a recent article in this journal, Thomas Finegan replies to our earlier article in this journal, which proposes a theological and ethical argument for the Catholic church to recognize same-sex civil unions as a lower-case sacrament. His critique focuses on the theological significance of embodiment as a one flesh union taught by Jesus, defended throughout Catholic tradition, and justified philosophically. We respond that Finegan’s critique misrepresents our argument and is mistaken biblically, anthropologically, and sacramentally, and suffers from scotosis.